2022
DOI: 10.1186/s40035-022-00322-0
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering lipid dysregulation in ALS: from mechanisms to translational medicine

Abstract: Lipids, defined by low solubility in water and high solubility in nonpolar solvents, can be classified into fatty acids, glycerolipids, glycerophospholipids, sphingolipids, and sterols. Lipids not only regulate integrity and fluidity of biological membranes, but also serve as energy storage and bioactive molecules for signaling. Causal mutations in SPTLC1 (serine palmitoyltransferase long chain subunit 1) gene within the lipogenic pathway have been identified in amyotrophic lateral sclerosis (ALS), a paralytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 260 publications
(560 reference statements)
0
18
0
Order By: Relevance
“…Recent reports have linked SPTLC1 variants with early‐onset ALS 10,11 . Among these reports, some specifically highlighted elevated ceramide levels as a contributing factor, 10 a notion supported by observations of increased ceramide levels in the plasma and spinal cords of patients with SALS 12 . These findings emphasize the integral role of lipid metabolism disturbances in ALS pathogenesis.…”
Section: Introductionmentioning
confidence: 87%
“…Recent reports have linked SPTLC1 variants with early‐onset ALS 10,11 . Among these reports, some specifically highlighted elevated ceramide levels as a contributing factor, 10 a notion supported by observations of increased ceramide levels in the plasma and spinal cords of patients with SALS 12 . These findings emphasize the integral role of lipid metabolism disturbances in ALS pathogenesis.…”
Section: Introductionmentioning
confidence: 87%
“…Recent studies have shown dysmetabolism of various lipid classes, such as fatty acids, glycerolipids, glycerophospholipids, sphingolipids, and sterols, in ALS patients (Agrawal et al., 2022; Liu et al., 2020; Nabizadeh et al., 2022). Lipids are believed to play a significant role in ALS pathogenesis and hold promise as both biomarkers and therapeutic targets.…”
Section: Lipid Metabolism and Alsmentioning
confidence: 99%
“…Up until now, our research has primarily focused on studying cholesterol metabolism and lipid abnormalities in MNs as related to ALS. However, it is important to note that neurons themselves do not store lipid droplets; instead, they receive lipids from astrocytes' lipid droplets during energy‐demanding situations (Agrawal et al., 2022). This raises the possibility that abnormalities in lipid metabolism within glial cells (astrocytes, oligodendrocytes, and microglia) may play a role in the development of ALS.…”
Section: Lipid Metabolism and Alsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple pathogenic mechanisms, including lipid dysregulation have been proposed to contribute to ALS (1,2,3,4). Indeed, dyslipidaemia and lipid dysregulation in the central nervous system and peripheral systems are prevalent in ALS patients, and have been reported to be clinically associated with disease severity, functional decline, and survival (3,4,5,6,7,8,9).…”
Section: Introductionmentioning
confidence: 99%